Public Policies, Gaps and Digital Literacy of the Elderly People: The Chilean Reality Observed from the Communes of Talca and San Joaquín (Law, State and Telecommunications Review, 2020)
Purpose ”“ In the current development of Chilean society there is a profound socio-demographic transformation, which implies an advanced aging of the population.Methodology ”“ According to the 2017 Census, 17.7 percent - equivalent to 1,586,634 women - are 60 years of age or older, while men in the same age group account for 14.7 percent (1,263,537). This age group constitutes an enormous challenge for the design of public policies.Findings ”“ It is necessary to generate access policies that take into account the different educational levels of older people in order to overcome the digital divide, as well as incentives for skills and competencies in the various uses and benefits currently provided by ICTs.